2016
DOI: 10.1515/jtim-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Management of hospitalized type 2 diabetes mellitus patients

Abstract: Both hyperglycemia and hypoglycemia in hospitalized patients are associated with adverse outcomes including increased rates of infection, longer hospital length of stay, and even death. Clinical trials in patients with type 2 diabetes mellitus proved that by improving glycemic control, we can reduce all of them. Insulin is the preferred treatment for glycemic control in most cases, but alternative treatment options that can normalize blood glucose levels without hypoglycemia are being sought. Moreover, hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…The study that is in line with the results of this study is a survival analysis study in Wahidin Sudirohusodo Makassar Hospital, with the conclusion that patients who are not on a diet have a greater risk of failure compared to those on a diet [23]. The recommendations on dietary aspects can contribute to achieve the desired blood glucose, blood pressure, lipid profile and weight [24]. Based on the level of dependency variable, the median survival in patients who perform self-care is 6 days.…”
Section: Fig 2 Kaplan Meier Curve Of Hypertension Statussupporting
confidence: 76%
See 1 more Smart Citation
“…The study that is in line with the results of this study is a survival analysis study in Wahidin Sudirohusodo Makassar Hospital, with the conclusion that patients who are not on a diet have a greater risk of failure compared to those on a diet [23]. The recommendations on dietary aspects can contribute to achieve the desired blood glucose, blood pressure, lipid profile and weight [24]. Based on the level of dependency variable, the median survival in patients who perform self-care is 6 days.…”
Section: Fig 2 Kaplan Meier Curve Of Hypertension Statussupporting
confidence: 76%
“…Otherwise stated, type 2 DM patients who on diet of DM need faster time to experience improvement in clinical conditions than those without diet of DM.The study that is in line with the results of this study is a survival analysis study in Wahidin Sudirohusodo Makassar Hospital, with the conclusion that patients who are not on a diet have a greater risk of failure compared to those on a diet[23]. The recommendations on dietary aspects can contribute to achieve the desired blood glucose, blood pressure, lipid profile and weight[24].…”
supporting
confidence: 70%
“…The recovery rates of prealbumin and albumin levels within 7 d after surgery were higher in patients of the modified B-ultrasound method group than in the traditional gastric juice withdrawal group. According to a multicenter survey that involved 26 hospitals in Europe, the nutritional status of patients was significantly negatively correlated with hospital stay, complications and mortality, and patients who received good nutritional support had shorter hospital stay, fewer complications and increased survival rate[ 52 - 55 ]. In the present study, the Kaplan-Meier survival analysis revealed that the complications of patients with good nutritional support were significantly fewer than those in the traditional gastric juice withdrawal group.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is a metabolic syndrome characterized by impaired glucose regulation resulting from insulin resistance and progressive loss of β-cells functionality. T2DM pharmacological protocols mainly target the endogenous response to glucose stimulation by increasing insulin sensitivity, insulin secretion, and glucose uptake ( Marín-Peñalver et al, 2016 ). However, the efficacy of such treatments is progressively reduced due to eventual pancreatic β-cells failure ( Kahn, 1994 ; Miller and Nguyen, 2014 ) and exogenous insulin administration is required.…”
Section: Introductionmentioning
confidence: 99%